Management of Arthrofibrosis After Total Knee Arthroplasty: Insights and Future Directions - Hoveidaei, Amir H.; Smitterberg, Chase W.; Misch, Monica; Katanbaf, Reza; Nace, James; Delanois, Ronald E.; Mont, Michael A. (The Journal of Knee Surgery, 2025)
Arthrofibrosis is a debilitating complication following total knee arthroplasty (TKA), affecting 3 to 13% of primary TKA patients and leading to 10% of revision surgeries. This review evaluates the current management strategies for arthrofibrosis, answering key questions on treatment modalities: (1) nonsurgical interventions, (2) arthroscopic and open surgical approaches, (3) revision procedures, and (4) adjunct and emerging therapies. Nonsurgical treatments, including aggressive physical therapy and continuous passive motion devices, show some improvements in range of motion (ROM), but long-term efficacy remains uncertain. Arthroscopic lysis of adhesions improves knee flexion by 26.7 to 51.2 degrees, with a mean final flexion of 100 to 103 degrees, but carries higher infection and revision risks. Open arthrolysis provides ROM improvements up to 43.4 degrees, with higher morbidity and complications. Revision TKA yields better functional outcomes, with mean flexion improvements of 15 to 25 degrees, but 43% of patients require further care. Emerging therapies, such as low-dose irradiation and pharmacologic agents like celecoxib and dexamethasone, show promise but require further validation. Despite advancements, gaps in high-quality data and standardized protocols persist, underscoring the need for more prospective trials.
Keywords: arthrofibrosis; total knee arthroplasty; management